2010
DOI: 10.1159/000314997
|View full text |Cite
|
Sign up to set email alerts
|

Women and Bone Health: Maximizing the Benefits of Aromatase Inhibitor Therapy

Abstract: Postmenopausal women with early breast cancer (EBC) are already at risk for bone loss, osteoporosis and fracture as they age because of declining estrogen levels. Adjuvant hormonal therapy with aromatase inhibitors (AIs; e.g. letrozole, anastrozole, exemestane) can exacerbate this risk. All three AIs appear to have similar effects on bone, increasing bone turnover and fracture risk in postmenopausal women with EBC. Risk factors for bone loss can be used to assess fracture risk and the need for ongoing assessme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 141 publications
1
7
0
Order By: Relevance
“…Also, treatment with letrozole resulted in significant bone loss: −3.3% and −5.3% (lumbar spine), and −1.4% and −3.6% (total hip) after the 1st and the 2nd year [26]. Decrease in BMD was apparently lower in patients treated with exemestane, possibly related to its steroidal structure: −1.7% and −1.0% (lumbar spine), and −1.4% and −0.8% (total hip) at 6 and 24 months, respectively [26]. These data were confirmed in a recent meta-analysis showing significant BMD reductions both at lumbar spine and total hip: −6.1% and −7.2% for anastrozole at 5 years, −5.3% and −3.6% for letrozole after 2 years, and −4.0% and −2.0% for exemestane at 2 years [27].…”
Section: Assessment Of Skeletal Effects Of Aromatase Inhibitorsmentioning
confidence: 98%
See 2 more Smart Citations
“…Also, treatment with letrozole resulted in significant bone loss: −3.3% and −5.3% (lumbar spine), and −1.4% and −3.6% (total hip) after the 1st and the 2nd year [26]. Decrease in BMD was apparently lower in patients treated with exemestane, possibly related to its steroidal structure: −1.7% and −1.0% (lumbar spine), and −1.4% and −0.8% (total hip) at 6 and 24 months, respectively [26]. These data were confirmed in a recent meta-analysis showing significant BMD reductions both at lumbar spine and total hip: −6.1% and −7.2% for anastrozole at 5 years, −5.3% and −3.6% for letrozole after 2 years, and −4.0% and −2.0% for exemestane at 2 years [27].…”
Section: Assessment Of Skeletal Effects Of Aromatase Inhibitorsmentioning
confidence: 98%
“…A comparative study analyzing data from the same pivotal trials found significant BMD reductions in patients under anastrozole: −2.3%, −4.0%, 6.08% (at lumbar spine) and −1.5%, −3.9%, −7.2% (total hip) after 1, 2, and 5 years, respectively [26]. Also, treatment with letrozole resulted in significant bone loss: −3.3% and −5.3% (lumbar spine), and −1.4% and −3.6% (total hip) after the 1st and the 2nd year [26]. Decrease in BMD was apparently lower in patients treated with exemestane, possibly related to its steroidal structure: −1.7% and −1.0% (lumbar spine), and −1.4% and −0.8% (total hip) at 6 and 24 months, respectively [26].…”
Section: Assessment Of Skeletal Effects Of Aromatase Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Some earlier animal research suggested that exemestane may have less effect on bone, 34 but subsequent research did not support this. 35,36 It is possible that exemestane was prescribed more in women who developed metastatic disease. We did not have data on metastatic disease to evaluate this hypothesis, but the time between BC diagnosis and AI initiation provided some evidence that exemestane was not used more frequently in the metastatic setting than letrozole (1080 days vs. 1524 days) but possibly was used more frequently than anastrazole (1080 days vs. 769 days).…”
Section: Discussionmentioning
confidence: 99%
“…Because AIs reduce bone density, women who are prescribed an AI are sometimes also prescribed a bisphosphonate,277 a type of medication that decreases bone resorption by disrupting osteoclast function 278. However, bisphosphonates can have serious side effects,279 so they are not prescribed merely as a matter of course 280.…”
Section: Medications Used For Redressing Side Effects Of Bc Treatmentsmentioning
confidence: 99%